Analisis Tingkat Pengungkapan Akun Persediaan dalam Laporan Keuangan Pemerintah Daerah di Jawa - Puji Suwarjuwono; Irwan Taufiq Ritonga (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
According to regulation Act No. 15/2004, adequate disclosure is one of the main criteria for the auditors in giving opinion for local government financial statements (LGFS). All accounts composing LGFS must be disclosed adequately. One of the most important accounts is inventory account in the balance sheet. This research aims to analyze whether the level of disclosure of inventory account is in accordance with the requirements of Government Accounting Standards Number 5 (GAS No. 5) on Inventory. This research uses descriptive qualitative approach. Documentation technique was utilized to collect 113 local government financial statements of regencies/cities in Java for fiscal year 2014. To analyze the data, this study employs percentage descriptive techniques. It was found that disclosure level of inventories account on local government financial statements in Java was still low and not in accordance with GAS No 5. Furthermore, there was no difference in the level of inventory disclosure among LGFS with unqualified opinion, qualified opinion, and disclaimer opinion. The average disclosure level of inventories for LGFS in Java amounted to 40,35%, with the highest disclosure level was 80,00% belonged to only two LGFS.